Schizophrenia dimension-specific antipsychotic drug action and failure in amphetamine-sensitized psychotic-like rats - Uzuneser, Taygun; Schindehuette, Magnus; Dere, Ekrem; von Hörsten, Stephan; Kornhuber, Johannes; Groemer, Teja W.; Müller, Christian P. (European Neuropsychopharmacology, 2018)
Schizophrenic patients suffer from various disruptions in their psyche, mood and cognition, most of which cannot be effectively treated with the available antipsychotic drugs. Some dimensions of the schizophrenia syndrome in man can be mimicked in animals by the amphetamine (AMPH)-sensitization-induced psychosis model. Using such a sensitization procedure, we induced a psychosis-like syndrome in rats, measured as a deficit in sensory information processing and memory deficits. We then investigated the possible restorative effects of continuous treatment with haloperidol (HAL), a typical antipsychotic drug, on distinct dimensions of the syndrome. We found that, continuous infusion of a clinically relevant dose of HAL (0.5 mg/kg/day) effectively ameliorated AMPH-sensitization-induced sensorimotor gating disruptions after seven days of treatment. However, the sensory information processing deficit reappeared after prolonged HAL treatment, suggesting a treatment failure in this dimension of the syndrome. HAL had at this dose little beneficial effects on the cognitive deficits. In contrast, a continuously administered low dose of HAL (0.05 mg/kg/day) successfully attenuated cognitive deficits, but aggravated the sensorimotor gating deficit under both short- or long-term treatment conditions. Post mortem neurochemical analysis revealed that the psychotic-like behavior induced by our manipulations might be explained by altered monoamine levels in distinct brain regions. These findings provide evidence for dissociating and dose-dependent HAL treatment action and failure at different dimensions of schizophrenia.
EVALuna2:36090